Cardiac surgery in the adult - Cohn, Lawrence H., 1937- (New York : McGraw-Hill Professional, 2012)
"Cardiac Surgery in the Adult guides residents and practicing surgeo ns through diagnosis, treatment and management as well as operative str ategy, decision-making, and technique in adult cardiac surgery. Develop ments in this field are constant and are in line with the surgical tren ds at large: less-invasive surgery with faster recovery times. Developm ents in this field include the use of robotic surgery, minimally invasi ve valve and coronary artery bypass surgery, stem-cell induced regenera tive medicine, tissue engineering and more, all of which are discussed and completely updated. Trends also take into account the demographics of the patient with an eye toward cross-training the surgeon in endovas cular skills by including topics such as percutaneous intervention and endovascular graft technology."--Provided by publisher.
Includes bibliographical references and index.
Keywords: Cardiac Surgical Procedures; Adult; Heart -- Surgery